Treatment of abdominal cellulite and circumference reduction with radiofrequency and dynamic muscle activation - Rungsima Wanitphakdeedecha (2018)
© 2015 Taylor & Francis Group, LLC. Background: Cellulite is a frequent skin condition for which treatment remains a challenge. A wide variety of treatments are available but most procedures offer suboptimal clinical effect and/or delayed therapeutic outcome. Only few therapeutic options have proven efficacy in the treatment of cellulite. Objective: To determine the efficacy and the safety profiles of radiofrequency and dynamic muscle activation technology in treatment of abdominal cellulite and circumference reduction. Methods: Twenty-five females with abdominal cellulite received 6 weekly radiofrequency and dynamic muscle activation treatments. Treatment areas included the abdomen and both sides of flanks. Subjects were evaluated using standardized photographs, and measurements of body weight and abdominal circumference at baseline, before every treatment visit, and 1 week and four weeks after the final treatment. Subcutaneous tissue thickness was recorded by ultrasound at baseline and 4 weeks after completion of treatment protocol. Physicians' evaluation and patient's satisfaction of clinical improvement were also measured. Results: All subjects completed the treatment protocol and attended every follow-up visits. There was significant abdominal circumference reduction of 2.96 and 2.52 cm at 1-, and 4-week follow-up visits (p < 0.05), respectively. At four weeks after the last treatment, the average circumferential reduction was sustained. Most of the patients were rated to have 25-49% improvement at 5th treatment, and 1- and 4-week follow-up visits. Ninety-two percent of the patients were satisfied with the treatment outcome. Conclusions: Radiofrequency provided beneficial effects on the reduction of abdomen and cellulite appearance. The benefit of muscle activation is yet to be determined.